Combined effect of volume fractions of nanofillers and filler-polymer interactions on 3D multiscale dispersion of nanofiller and Payne effect. (January 2022) - Li, Xiangyan; Tian, Chenchen; Li, Han; Liu, Xinyang; Zhang, Liqun; Hong, Song; Ning, Nanying; Tian, Ming
Graphical abstract: Abstract: Payne effect is often used to indirectly reflect the micro-dispersion of nanofillers at small strains in elastomer nanocomposites. However, the relationship between the Payne effect and the three-dimensional (3D) dispersion of nanofillers has not been fully understood. To deeply understand this relationship, the combined effect of the volume fraction of nanofillers ( φf ) and the filler-polymer interfacial interactions ( If-p ) on the 3D multiscale dispersion parameters of nanofillers were characterized via a combination of three dimensional-Scanning Transmission Electron Microscopy and synchrotron radiation X-ray computed tomography. Results show whatever the φf is, the higher If-p contributes to the higher branching degree and connectivity of agglomerates/networks. When the φf is below or around the percolation threshold (PT), the higher If-p contributes to the lower compactness and larger agglomerates, but the effect of If-p on the homogeneity of silica (SiO2 ) is different. When the φf is below PT, as the If-p increases, the size of agglomerates increases, and the homogeneity of SiO2 decreases. When the φf is around PT, as the If-p increases, the size of agglomerates increases, and the homogeneity of SiO2 also increases. The relationship between the Payne effect and 3D multiscale dispersion of nanofillers was revealed. It was found that the dispersion of SiO2 can be reflected by the Payne effect only when the φf is around the PT. The higher branching degree, and connectivity of the agglomerates/networks under higher If-p results in stronger Payne effect.